2019
DOI: 10.1016/j.rmr.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab et immunothérapie allergénique : cas clinique et revue de la littérature

Abstract: Déclaration de liens d'intérêts :Au cours des 5 dernières années, Pascal DEMOLY a perçu des honoraires ou financements pour participation à des congrès, communications, actions de formation, conseil, participation à des groupes d'experts, de la part les Laboratoires ALK et Stallergenes Greer. Au cours des 5 dernières années, Pascal DEMOLY a été investigateur principal, coordonnateur, responsable scientifique d'études cliniques promues par les Laboratoires ALK et Stallergenes Greer. Au cours des 5 dernières ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…30 French authors reported a pediatric female patient affected by severe allergic asthma successfully treated with sequential therapy with omalizumab and AIT to Alternaria, who maintained an asthma control for a long time after cessation of omalizumab. 31 Lambert et al reported data from six patients (11-21 years) with severe persistent asthma treated with omalizumab who received SCIT to house dust mite (HDM) under a clustering protocol during omalizumab treatment, then SCIT maintenance alone after biological therapy discontinuation. 83% of the population pretreated with omalizumab did not present severe side effects; one patient discontinued SCIT because of uncontrolled asthma.…”
Section: Discussionmentioning
confidence: 99%
“…30 French authors reported a pediatric female patient affected by severe allergic asthma successfully treated with sequential therapy with omalizumab and AIT to Alternaria, who maintained an asthma control for a long time after cessation of omalizumab. 31 Lambert et al reported data from six patients (11-21 years) with severe persistent asthma treated with omalizumab who received SCIT to house dust mite (HDM) under a clustering protocol during omalizumab treatment, then SCIT maintenance alone after biological therapy discontinuation. 83% of the population pretreated with omalizumab did not present severe side effects; one patient discontinued SCIT because of uncontrolled asthma.…”
Section: Discussionmentioning
confidence: 99%